(untitled) (Heritage, 2022)
The subject of this article is the analysis of characters of deformed intellectuals and the problem of spiritual crisis in stories of A.P. Cehov and Laza Lazarevic. By reviewing of attitudes of Cehov`s and Lazarevic`s heroes researchers, in the introduction of the article the term of ``the house of the routine``, introduced by Russian critics of Cehov`s work, Kamcatnov and Smirnov and which can be also applied in interpretation of Lazarevic`s characters, is explained. In the main part of the article there were analyzed characters from the stories of A.P. Cehov Gooseberry, Jonic, House with mezzanine and of Laza Lazarevic The wind, Verter and German woman. One can conclude that emotion alstates of the heroes, between the other things, direct the complex of supremacy. In the conclusion it was pointed on similarities and peculiarities of the heroes and all the time actuality of the problem of spiritual crisis of intellectual’s.